The Study of Zahiriddin Muhammad Babur’s Works in Turkey (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the research of Zahiriddin Muhammad Babur's work in Turkey, the attention of Turkish scholars to Babur's legacy, translations, scientific research and publications. It also shows the place of Babur's scientific legacy in Turkish literary studies. Furthermore, the article examines the methodological approaches applied by Turkish researchers, the evolution of Babur studies over different periods, and the contribution of Turkish academia to the global understanding of Babur’s intellectual and cultural influence. In addition, it evaluates the role of comparative literature and historical-philological analysis in deepening the study of Babur’s oeuvre in Turkey, emphasizing the importance of continued academic engagement with his works.